Hybrid imaging for detection of carcinoma of unknown primary: A preliminary comparison trial of whole-body PET/MRI versus PET/CT. Issue 11 (November 2016) - Ruhlmann, Verena; Ruhlmann, Marcus; Bellendorf, Alexander; Grueneisen, Johannes; Sawicki, Lino M.; Grafe, Hong; Forsting, Michael; Bockisch, Andreas; Umutlu, Lale
Highlights: Both 18F-FDG PET/CT and 18F-FDG PET/MRI provide a comparable diagnostic ability for detection of primary cancer and metastases in CUP-syndrome. Both imaging methods showed comparably high lesion conspicuity and diagnostic confidence (superior assessment of cervical lesions in PET/MRI). PET/MRI may serve as a powerful alternative, particularly for therapy monitoring or surveillance considering the long-term cumulative dose. Abstract: Purpose: The aim of this study is to evaluate and compare the diagnostic potential of integrated whole-body [18F]FDG-PET/MRI to [18F]FDG-PET/CT for detection of a potential primary cancer and metastases in patients suspected for cancer of unknown primary (CUP). Methods: A total of 20 patients (15 male, 5 female, age 53 ± 13 years) suspect for CUP underwent a dedicated head and neck & whole-body [18F]FDG-PET/CT (Biograph mCT 128, Siemens Healthcare) and a subsequent simultaneous [18F]FDG-PET/MRI examination (Biograph mMR, Siemens Healthcare). Two readers rated the datasets (PET/CT; PET/MRI) regarding the detection of the primary cancer and metastases, lesion conspicuity (4-point ordinal scale) and diagnostic confidence (3-point ordinal scale). PET analysis comprised the assessment of maximum standardized uptake values (SUVmax) of all PET-positive lesions using volume of interest (VOI) analysis derived from the PET/CT and PET/MR datasets. All available data considering histology and imaging including prior and clinical follow-up examinations served as reference standard. Statistical analysis included comparison of mean values using Mann-Whitney U test and correlation of SUVmax using Pearson's correlation. Results: In 14 out of 20 patients 49 malignant lesions were present. The primary cancer could be correctly identified in 11/20 patients with both PET/CT and PET/MRI. PET/CT enabled the detection of a total 38 metastases, PET/MR respectively of 37 metastases (one lung metastasis <5mm was missed). PET/CT and PET/MRI showed comparably high lesion conspicuity (2.6 ± 0.6 each), with superior assessment of cervical lesions in PET/MRI and an indicated superior assessment of pulmonary lesions in PET/CT. Diagnostic confidence was rated comparably high in PET/CT and PET/MRI (2.7 ± 0.5 each). The mean values of SUVmax of all PET-positive lesions (PET/MRT 7.9 ± 4.2 vs. PET/CT 7.2 ± 3.5) showed a strong positive correlation between the SUVs derived from both hybrid imaging systems (Pearson's correlation r = 0.927). Conclusions: Both hybrid imaging techniques provide a comparable diagnostic ability for detection of primary cancer and metastases in patients with CUP, with comparably high lesion conspicuity and diagnostic confidence, offering superior assessment of cervical lesions in PET/MRI and potentially of pulmonary lesions in PET/CT. Furthermore, due to the significantly lower dose of ionizing radiation, PET/MRI may serve as a powerful alternative to PET/CT, particularly for therapy monitoring and/or surveillance considering the long-term cumulative dose.